The Endophytic Symbiont—Pseudomonas aeruginosa Stimulates the Antioxidant Activity and Growth of Achyranthes aspera L. - Devi, Khaidem A.; Pandey, Garima; Rawat, A. K. S.; Sharma, Gauri D.; Pandey, Piyush (Frontiers in Microbiology, 2017)
A plant growth promoting bacterial endophyte designated as AL2-14B, isolated from the leaves of Achyranthes aspera L. was identified as Pseudomonas aeruginosa based on its phenotypic and physiological features, and 16S rRNA gene sequence analysis. AL2-14B had plant growth stimulating attributes including - siderophore and indole acetic acid release, inorganic phosphate solubilization, along with nitrogenase, ammonification, and protease activities. It also exhibited antifungal property against Rhizoctonia solani. The plantlets grown in germ-free condition were inoculated with AL2-14 B and studied for the colonization of endophyte. Significant increase in population of AL2-14 B between 3rd to 5thdays after inoculation was recorded. The treatment of plants with endophytic P. aeruginosa AL2-14 B increased Nitrogen, Phosphorus, Potassium (NPK) contents in plant by 3.8 %, 12.59 %, and 19.15% respectively. Significant enhancement of shoot and root length, dry leaf, dry shoot and dry root weight and leaf surface area as compared to control (P<0.05) was recorded in AL2-14 B inoculated plants. The antioxidant activities increased in plants grown in germ-free conditions and inoculated with AL2-14 B. The present study emphasizes on the role of diazotrophic endophyte P. aeruginosa AL2-14 B in stimulating growth of A. aspera L. and improvement of its medicinal properties. Significant increase in growth and antioxidant content of P. aeruginosa AL2-14 B treated plants suggests the possibility of an economical and eco-friendly mean of achieving antioxidants rich, healthier A. aspera plants.